Briófitas epífitas sobre palmeiras em diversos ecossistemas no estado do Pará, Brasil - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2008)
The research group on bryophytes in Eastern Amazonia has worked in different areas in Pará. All this effort has resulted in a significant increase in the knowledge of the diversity of bryophytes that occur in the various natural ecosystems and in areas that have suffered intense anthropic action in the state. It was found, however, that there are still no studies for the region relating the different tree species that serve as phorophytes to the bryophyte species collected on them. Among the arboreal phorophytes used by bryophytes are palm trees. Palm trees gather an expressive number of species in the Amazon region, deeply marking the landscape of the region, due to their ecophysiological and morphological adaptations that allow them to colonize almost all Amazonian environments. The aim of this work is to inventory the epiphytic bryophytes that occur on palm species in different Amazonian ecosystems, evaluating their diversity and verifying possible associations, in addition to contributing to the knowledge of bryophytes in the state of Pará. Specimens from different areas of the State were studied, which are deposited in the herbarium João Murça Pires (MG) and new collections were made on Murutucu Island, Belém. To date, 101 samples have been worked on, of which 67 were from the municipalities of Cachoeira do Arari and Soure (Marajó), selected because they were collected on palm trees. From this material, 9 species of liverworts were identified, distributed in 7 genera and 1 family, and 13 species of mosses, distributed in 6 genera and 3 families. The rest of the samples studied (34) were collected on Murutucu Island, for which 25 species of liverworts were identified, distributed in 10 genera and 2 families, and 5 species of mosses, distributed in 5 genera and 4 families. The leafy liverwort, Frullanoides corticalís (lehrn. & lindenb.) van Slageren, stood out for being a new occurrence for the state of Pará. It was observed that the inajá and açaí palms presented a greater amount of bryophytes, both in number of species and specimens. These results are not yet conclusive, since there are still samples to be worked on and collections to be made.
Epiphytic bryophytes on palm trees in different ecosystems in the state of Pará, Brazil
Keywords: Musgos; Hepáticas; Palmeiras; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA